Social Justice for Children in the South - Tonon, Graciela H. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book considers that contextual factors are important for the achievement of social justice and it recognizes that vulnerability to which children are exposed is a phenomenon throughout the planet, particularly in the South. It presents a theoretical review of social justice as well as different situations of vulnerability children experience in their daily lives in which they can be injured, affecting their well-being and the exercise of their rights. It examines the impact of the COVID-19 pandemic on children, considered as a vulnerable group warranting special social policy considerations. It also presents the need to change power structures in knowledge production and decision-making processes to achieve social justice for children; the importance of investing in children; the exclusion of children from participation in certain activities and the shame of not being able to participate in equal conditions with others; the lives of migrant children belonging to ethnic minorities exposed to language barriers and access to technological devices; and the analysis of the process of social re-integration of children from conditions of armed conflict. The book concludes that governments need to assume social justice as part of universal human interests, providing security, conditions for well-being, and guaranteeing social justice for all children.
Children's Social Vulnerability and Social Justice in the South -- Social Justice as a State Policy: Children's Rights in South America -- Public Spending and Investment in Children: Measuring and Assessing Social and Economic Justice -- A Social Justice Perspective on Children's Well-Being: Considerations for Children's Rights in the Context of COVID-19 -- The Daily Life of Children During the Confinement Stage due to the Covid 19 Pandemic -- Towards a Nuanced Understanding of Children's Participation and Realizing Social Justice in the Urban Realm: A Case Study in the Classroom with Ethnic Minority Children -- Child Soldiers as Victims or as Perpetrators? An Analysis of the Case of Colombia -- Adolescents' Expectations and Wellbeing Perceptions in Mumbai's Hinterland and its Slums. What Means 'To Become Someone' in Early XXI Century in Maharashtra? -- Children as Capable Agents and Citizen: Empowering Children and Youth Mario Biggeri and Caterina Arciprete -- Social Justice - from Potential To Practice. The Shared Benefit of Change for Children.
Keywords: Human rights; Social structure; Equality; Social policy; Quality of life; Developmental psychology; Human Rights; Social Structure; Global Social Policy; Quality of Life Research; Child and Adolescence Psychology